A Natural Variant of the T Cell Receptor-Signaling Molecule Vav1 Reduces Both Effector T Cell Functions and Susceptibility to Neuroinflammation. - Sahar Kassem; Guillaume Gaud; Isabelle Bernard; Mehdi Benamar; Anne S Dejean; Anne S Dejean; Roland Liblau; Gilbert J Fournié; Céline Colacios; Bernard Malissen; Abdelhadi Saoudi (PLoS Genetics)
The guanine nucleotide exchange factor Vav1 is essential for transducing T cell antigen receptor signals and therefore plays an important role in T cell development and activation. Our previous genetic studies identified a locus on rat chromosome 9 that controls the susceptibility to neuroinflammation and contains a non-synonymous polymorphism in the major candidate gene Vav1. To formally demonstrate the causal implication of this polymorphism, we generated a knock-in mouse bearing this polymorphism (Vav1R63W). Using this model, we show that Vav1R63W mice display reduced susceptibility to experimental autoimmune encephalomyelitis (EAE) induced by MOG35-55 peptide immunization. This is associated with a lower production of effector cytokines (IFN-γ, IL-17 and GM-CSF) by autoreactive CD4 T cells. Despite increased proportion of Foxp3+ regulatory T cells in Vav1R63W mice, we show that this lowered cytokine production is intrinsic to effector CD4 T cells and that Treg depletion has no impact on EAE development. Finally, we provide a mechanism for the above phenotype by showing that the Vav1R63W variant has normal enzymatic activity but reduced adaptor functions. Together, these data highlight the importance of Vav1 adaptor functions in the production of inflammatory cytokines by effector T cells and in the susceptibility to neuroinflammation.